1995
DOI: 10.1098/rstb.1995.0006
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific recombination and circular chromosome segregation

Abstract: The Xer site-specific recombination system functions in Escherichia coli to ensure that circular plasmids and chromosomes are in the monomeric state prior to segregation at cell division. Two recombinases, XerC and XerD, bind cooperatively to a recombination site present in the E. coli chromosome and to sites present in natural multicopy plasmids. In addition, recombination at the natural plasmid site cer, present in ColEl, requires the function of two additional accessory proteins, ArgR and PepA. These access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(36 citation statements)
references
References 14 publications
0
35
0
1
Order By: Relevance
“…coli plasmids employ the same pair of resolution enzymes, XerC and XerD, to monomerize; accessory proteins determine the directionality of the reaction in the plasmid systems (67). No such directionality-determining proteins are known for the chromosomal dimer resolution, suggesting that the chromosomal system is guided by a different kind of signal.…”
Section: Homologous Recombination In Phage T4mentioning
confidence: 99%
See 1 more Smart Citation
“…coli plasmids employ the same pair of resolution enzymes, XerC and XerD, to monomerize; accessory proteins determine the directionality of the reaction in the plasmid systems (67). No such directionality-determining proteins are known for the chromosomal dimer resolution, suggesting that the chromosomal system is guided by a different kind of signal.…”
Section: Homologous Recombination In Phage T4mentioning
confidence: 99%
“…David Sherratt spoke about the chromosome of E. coli, where the dimers are resolved to monomers by a two-enzyme sitespecific recombination system, acting on the dif site in the replication terminus (7,67). XerC recombinase makes a halfcrossover (a Holliday junction) between two dif sites on the sister chromatids, whereas XerD recombinase, acting on this Holliday junction, splits the ''figure-eight'' chromosome into two monomers.…”
Section: Homologous Recombination In Phage T4mentioning
confidence: 99%
“…Subsequently, it was shown that one of these site-specific recombination systems, XerCD site-specific recombination, also functions in the conversion of dimeric Escherichia coli chromosomes to monomers (4-6). Xer recombination uses two related recombinases, XerC and XerD, belonging to the tyrosine recombinase family, each recombinase catalyzing the exchange of one pair of strands in a reaction that proceeds through a Holliday junction (HJ) intermediate (7)(8)(9). XerCD act at the recombination site dif, located in the replication terminus region of the E. coli chromosome and at related sites in multicopy plasmids, for example, psi in plasmid pSC101 and cer in ColE1 (3, 10).…”
mentioning
confidence: 99%
“…The Xer site-specific recombination system of Escherichia coli resolves multimeric forms of circular replicons to allow efficient segregation to daughter cells at cell division (Summers and Sherratt, 1984;Sherratt et al, 1995). Two recombinases, XerC and XerD, act at the chromosomal site dif and at plasmid-borne sites, such as cer of ColE1 and psi of pSC101 (Colloms et al, 1990;Blakely et al, 1991;1993;Kuempel et al, 1991;Cornet et al, 1994).…”
Section: Introductionmentioning
confidence: 99%